PENGARUH MEDIA AUDIO VISUAL TERHADAP PERKEMBANGAN AFEKTIF KOGNITIF DAN PSIKOMOTOR SISWA DALAM PEMBELAJARAN PERMAINAN FUTSAL - Michael Johannes H. Louk; Erwin Sarnoto Neolaka; Salmon Runesi (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2020)
ABSTRACTThe purpose of this study is to study the effect of audio visual media on the cognitive and psychomotor affective development of students. The method used in this research is experiment. The population in this study were all students who took part in futsal extracurricular activities at SMPN 11 Kota Kupang while the sample in this study was 40 male students. The instrument used used the game performance assessment test (GPAI) and the instrument transferred from Permana (2014, p. 37). Data were processed using SPSS version 22. The results of this study are: 1) Increased affective participation from the control group 48.64% to the trial 49.58%, by proving 27.77%. 2) With the increase in cognitivefrom the control group 22.07% to the experiment 33.47% with the experiment 59.18%. 3) Increase in psychomotor development from the control group 17.08% to the 19.79% experiment with the 31.03% trial. So this shows a significant increase of learning outcomes through audio-visual media on the affective, cognitive and psychomotor development in futsal learning.Keywords: Audio Visual, Affective, Cognitive, Psychomotor, Futsal Learning.